Embracing Online Virtual Microscopy and Web Conferencing for Pathology Residents in Thailand: A Paradigm Shift in Pathology Education in The Midst of COVID-19 Pandemic - Kantasiripitak, Charinee; Laohawetwanit, Thiyaphat (Asian Medical Journal and Alternative Medicine, 2021)
Pathology residents and pathologists used digital pathology, a web conferencing software, and an online game-based learning platform during an online seminar held by the Royal College of Pathologists of Thailand during the COVID-19 pandemic. They had satisfactory performance and viewed these technological advances as potential modalities for pathology education.